High involvement work system and organizational and employee resilience: Impact of digitalisation in crisis situations - Nguyen, M.; Malik, A.; Sharma, Piyush; Kingshott, Russel; Gugnani, R. (2024)
This study investigates the mediating role of employee perceptions about their power, information, rewards, and knowledge (PIRK) in the impact of high involvement work systems (HIWS) on organizational resilience and employee outcomes, and the moderating role of transformational leadership in this process. We find support for most of our hypotheses using data collected from 379 employees in a technologically-mediated work context. Specifically, HIWS's focus on teamwork and training enhances employee perceptions of power, information, rewards, and knowledge sharing, which in turn leads to higher organizational resilience and employee outcomes comprising job performance and satisfaction, and positive mental health and retention. The study also confirms the mediating role of employee perceptions of PIRK and the moderating effect of transformational leadership. This study contributes to the growing HIWS literature by extending its conceptual definition and linking it to organizational resilience and employee outcomes through employee perceptions of PIRK. We also discuss that involving employees in decision-making during the digitalization process may help improve organizational and employee resilience in crisis situations.